Pengaruh Terapi Lingkungan Terhadap Tingkat Ketergantungan pada Lansia Depresi di BSLU Meci Angi Bima - Wahidah, Wahidah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Environmental Therapy is an act of healing patients through manipulation and modification of elements in the environment and has a positive effect on the individual's physical and psychological well-being and supports the healing process. Addiction is placing trust in other people or other objects, for continuous assistance, reassurance in meeting needs. This study used purposive sampling, which means determining the sample by selecting a sample from among the population according to what the researcher wanted, so that the sample could represent the characteristics of the previously known population. The research instrument used a questionnaire, used the Wilcoxon test and the data was analyzed using SPSS 16. Statistical test results showed that before being given environmental therapy and after being given (post test) there was an increase in the value of p = 0.000, which means that there was an effect of environmental therapy on the level of dependence on depressed elderly at BSLU Meci Angi Bima. This environmental therapy is so effective that it changes the level of dependency in depressed elderly people.